2016
DOI: 10.1371/journal.pntd.0005146
|View full text |Cite
|
Sign up to set email alerts
|

Development of a PCR Assay to Detect Low Level Trypanosoma cruzi in Blood Specimens Collected with PAXgene Blood DNA Tubes for Clinical Trials Treating Chagas Disease

Abstract: Chagas disease is caused by the parasitic infection of Trypanosoma cruzi (T. cruzi). The STOP CHAGAS clinical trial was initiated in 2011 to evaluate posaconazole in treating Chagas disease, with treatment success defined as negative qualitative PCR results of detecting the parasites in blood specimens collected post-treatment. PAXgene Blood DNA tubes were utilized as a simple procedure to collect and process blood specimens. However, the PAXgene blood specimens challenged published T. cruzi PCR methods, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
(14 reference statements)
0
17
0
Order By: Relevance
“…efficiency from both serial dilution experiments confirmed that our standard curve assay was robust and repeatable (Bustin et al, 2009). In this study, we defined the analytical limit of detection (LoD) as the lowest concentration where at least 95% of the technical replicates were positive in the Ter-qPCR (Wei et al, 2016). The LoD was calculated from serial dilutions of Terplasmids.…”
Section: Ter-qpcr Analytical Specificity Sensitivity and Efficiencymentioning
confidence: 65%
See 2 more Smart Citations
“…efficiency from both serial dilution experiments confirmed that our standard curve assay was robust and repeatable (Bustin et al, 2009). In this study, we defined the analytical limit of detection (LoD) as the lowest concentration where at least 95% of the technical replicates were positive in the Ter-qPCR (Wei et al, 2016). The LoD was calculated from serial dilutions of Terplasmids.…”
Section: Ter-qpcr Analytical Specificity Sensitivity and Efficiencymentioning
confidence: 65%
“…In this study, we defined the analytical limit of detection (LoD) as the lowest concentration where at least 95% of the technical replicates were positive in the Ter-qPCR ( Wei et al, 2016 ). The LoD was calculated from serial dilutions of Ter-plasmids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some acquired conditions are known to modify the results of PCR assays in patients with Chagas disease, such as co-infection with helminths, infection with human immunodeficiency virus, immunosuppression and pregnancy [1417]. In the last 15 years a strong effort has been made in validation and standardization of these techniques, reaching a sensitivity of 60–90% for the best performing methods, with a specificity of 100% [18, 19]. In our study, pre-treatment PCR was performed in 73% of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…False negatives occur due to fluctuations in parasitemia, the isolation of parasite in tissue or organs, and the intrinsic limit of detection of PCR and qPCR techniques [58]. Other distinct factors may contribute to the overall performance of PCR assays: the size of the serum sample for parasite DNA extraction, the sample collection tubes, the different PCR assay conditions, and the algorithm used to classify results can affect the evaluation of the samples, as was demonstrated by Wei et al [59] for the STOP CHAGAS clinical trial that evaluated posaconazole for the treatment of CD [60]. Nevertheless, PCR is a promising tool that can be easily performed in clinical settings and used for clinical trials; thus, the investment in improving PCR methodologies is worthwhile.…”
Section: Parasite Dna Amplification and Antigens For Serological Testsmentioning
confidence: 99%